Technical-economic prefeasibility of an olive pomace biorefinery for the main olive-growing areas of Argentina - Monetta, P. (2024)
Fil: Monetta, P. Instituto Nacional de Tecnología Agropecuaria. Estación Experimental Agropecuaria San Juan (INTA-EEA San Juan); Argentina